The effect of process parameters in extruding scaffold design using synthetic biomaterials - Mohd Ariffin, Khairul Anuar; Sukindar, Nor Aiman; Baharudin, B.T. Hang Tuah; Jaafar, Che Nor Aiza; Ismail, Mohd Idris Shah (ModTech Publishing House, 2019)
Open-source 3D printers have become a popular technology for inexpensively and rapidly fabricating threedimensional products, including those for medical use. We developed and tested a nozzle for extruding synthetic biomaterials for fabricating scaffold structures that can be used as a medium for cell growth in, for instance, orthopedic replacements. The nozzle was designed iteratively to optimise the die angle, nozzle diameter, and liquefier shape for extruding bioresorbable polymers, and a thermal insulator was installed to maintain consistent temperature in the liquefier chamber. We then fabricated a range of scaffold structure parts with varying percentages of infill material and infill patterns. Analysis of variance tests show that the percentage of infill is a dominant factor affecting the porosity as well as the mechanical properties of the samples. Samples with 10%–30% of infill with a combination of lined infill patterns exhibited 50%–70% porosity with 12–20 MPa compressive strengths. These specifications are well-suited for cell growth. To demonstrate the feasibility of fabricating structures with consistent porosity with open-source printers, a humerus bone was 3D printed using both Polylactic acid (PLA) and polymethylmethacrylate (PMMA) filament, and the porosity was controllable. This study suggests that opensource 3D printers may be used for printing bone replacements in the near future.